Digital Marketing Communication Innovation: A Gender Bias on @Mbasiticom Instagram Content - I Gede Arya Pering Arimbawa; Muh. Najib Husain; Nurhayati; Ari Usman; Dendi Pratama (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
Marketing innovation recently occurred and had well growth in social media due to digital marketing efficiency and social media’s spread in producing informative content. Household servant industry is part of it with the content of @Mbasiticom Instagram account frequently produce content of their services that show a new change in marketing and also an innovation in marketing field, However, as household servant industry is known as exploitative in their respective field, @mbasiticom doesn’t escape this system which causing harmful stigma between women and society. With the content analysis, a new perspective is discovered upon the industry, how women and gender equality study is still relevant even to this day.